Baixo São Francisco : navegação, pesca e seus (des)dobramentos - Araujo, Adriano Morais (2019)
The São Francisco River, known as the National Integration River, has a strong connection with navigation, its history is marked by the continuous use of water, as a connecting element between the north and south of the country that creates and strengthens communication, settlement and harnessing natural resources. The objective of this research was to analyze how resources and problems associated with river navigation from the collaboration of artisanal fishermen in the lower São Francisco. For this, it was necessary to identify the socioeconomic profile of artisanal fishers and how their experiences with the river, in addition to highlighting the importance of untreated navigation and the problems related to navigation and fishing of artisanal optical fish. To verify the types of use, as it still exists, navigation selects a stretch of navigable course in the river within a given physiographic clipping of the basin. The starting point of the process was blocked by the Xingó hydroelectric dam, ending the process between the Niterói people in Sergipe and the Alagoas municipality of Pão de Açúcar. To collect data, the questionnaires were semi-structured with fishermen and canoe masters. Please note that navigation suffers from the effects of leakage changes, hinders or completely hinders use, especially on larger vessels. Depending on the flow, the river presents great difficulties for navigation, but does not prevent its realization, taken into consideration by the small boats of fishermen and tourism companies. The fishermen of the municipalities visited were fundamental for the development of research, because they perform their work activities daily and, therefore, have a deep knowledge and a significant perception of the nuances that the river presents. The speech of the interviewed communities confirms how the number of participants in the fishing and fishing process, mainly from the construction of buses along the São Francisco River. Among the main problems raised were: concentration of sludge, stones, sandbanks and reduction in fish production. These impacts cause several damages to local communities, which reflect the reduction of fishing potential, generating conflicts of use in the region.